Health care practices in the face of childhood autism (Research, Society and Development, 2023)
The objective was to identify how health professionals provide assistance to children diagnosed with autism. This is a                 bibliographic review research, narrative, exploratory and with a qualitative approach. Performed by searching the following databases: Latin American and Caribbean Literature in Health Sciences (Lilacs), Nursing Database (BDENF) and Scientific Electronic Library Online (SciELO), all via the Virtual Health Library (VHL). ), being a library that brings together several databases. To search within these databases, some Health Sciences Descriptors (Decs) were used, namely: "Autism", "Childhood Autism", "Autistic Spectrum Disorder", "Health Professionals", "Health Care Mental” and “Health Care”, in association with the Boolean operator AND and OR. With this, it is      understood that the role of professionals working in the health area is to ensure that the family's needs are met from diagnosis to treatment. with qualified listening, the creation of bonds with the child and with the parents, the early identification of signs for the previous diagnosis, the support before such a diagnosis, the performance of interventions, the stimulus to the search for support groups, and mainly, the I encourage them to overcome limitations, according to the unique evolution of each child.